Comparing Housing Market Dynamics in the Irish and UK Residential Markets - Disch, Wendy; Egan, Paul; McQuinn, Kieran; Kenny, Eoin (The Economic and Social Review, 2024)
Given the sharp and persistent increase in both house prices and rents, the need to increase housing supply in the Irish market has become increasingly pressing over the last number of years. While a number of Government policy initiatives have been introduced, it is clear that actual levels of housing supply are still somewhat below the level of demand, with official Government targets suggesting a significant difference between the two. Given the difficulties experienced by the supply side of the domestic housing market, it is informative and interesting to contrast housing supply in the Irish market with that of Ireland’s nearest housing markets; in particular, the Northern Irish, English, Scottish and Welsh markets. These markets share many of the characteristics of the Irish market in terms of planning and regulatory regimes as well as cultural preferences for certain property types compared with continental housing markets. In this paper we, therefore, build on previous work by Egan and McQuinn (2023a) to assess the relationship between house prices and supply levels across the different Irish and UK markets. This serves as an important benchmark by which to evaluate the performance of the supply side of the Irish residential market.